Information Literacy of Postgraduate Students in Online Learning - M Akbar Gulvara; Abdul Rasyid Fakhrun Gani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the tendency of students' information literacy in finding and retrieving information, sources of information, and using information. The population in this study were students of the Mathematics Education Study Program at one university in West Java Province class of 2021-2022, the sample was taken as many as 30 students using convenience sampling technique. This research is included in qualitative research with data collection techniques in the form of questionnaires distributed using google form. The data was processed descriptively qualitatively by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that 72.16% of students are able to search for information well, 69.49% of students are able to manage information well, and the most widely used sources of information by Mathematics Education students in university of West Java Province are online journals, printed books, and digital libraries. The conclusion in this study is that students already have information literacy during online learning in the 2021/2022 school year, but still need to improve the quality of learning to maximize students' use and management of information